THE INFLUENCE OF LEADERSHIP STYLE ON GROUP MOTIVATION TO INNOVATE DIGITALLY AT COFFEE PUNTANG WANGI BANDUNG DISTRICT - Azzahra, Calista Luky; Junipriansa, Donni; Yasmin, Namira Fisilmi (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2025)
Campakamulya Village, situated at the base of Mount Puntang in Bandung Regency, is a prominent producer of high-quality coffee with a distinctive flavor profile. The Ormawa Membangun Negeri (POMN) Program is strategically positioned to facilitate digital transformation and foster innovation within the Puntang Wangi Coffee group amid the difficulties of the digital age. The Head of the Forest Village Community Institution (LMDH) facilitates this change process by fostering cooperation between students and the coffee group, therefore establishing a pleasant synergy.This research seeks to examine the impact of leadership style on group motivation in the adoption of digital technologies. This research, using a quantitative methodology and data analysis via SPSS software, found that leadership style significantly influences group motivation. The study instrument demonstrated substantial validity and reliability, indicating strong internal consistency.The findings of this research affirm that leaders who proficiently enable cross-group communication may enhance the adaption of digital technologies. Recommendations include enhancing the role of group leaders in facilitating collaboration-oriented digital transformation. Future study should investigate organizational culture variables and intergroup interactions to enhance the durability of digital innovation.